(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
The study investigated the linguistic experiences of the women food vendors in the informal sector in Katutura who identified themselves as monolingual speakers of the Oshiwambo language. The aim is to explore how the business activities of these women are affected by their inability to speak an additional language. The aim was to establish how monolingual women manage to run their businesses in a multilingual setting. The study was qualitative and the instruments used consisted of a questionnaire that solicited the linguistic repertoires, biographic information and contact details of the participants and semi-structured interviews to discuss the participants’ language experiences concerning their business activities in the market. The study revealed that the participants were, in actual fact, not monolingual because they had knowledge of other languages in their repertoires; the participants’ business activities were not hindered by their inability to speak an additional language fluently because they mix words of the languages in their linguistic repertoire to communicate instead of speaking in one language.